Style : an approach to appreciating theatre - Wallace, E. Bert (New York : Routledge, Taylor & Francis Group, 2022)
"Style: An Approach to Appreciating Theatre offers brief, readable chapters about the basics of theatre as a starting point for discussion, and provides new adaptations of classic plays that are both accessible to students learning about theatre and fit for production. In this text, style is the word used to describe the various ways in which theatre is done in real space and time by humans in the physical presence of other humans. The book uses style, the "liveness" of theatre that makes it distinct from literature or history, as a lens to see how playwrights, directors, designers, and actors bring scripts to life on stage. Rather than focusing on theatre history or literary script analysis, it emphasizes actual theatrical production through examples and explores playscripts illustrating four theatrical styles: Realism, Theatricalism, Expressionism, and Classicism. Susan Glaspell's Realistic play Trifles is presented as written, while The Insect Play by the Brothers Čapek, The Hairy Ape by Eugene O'Neill, and Antigone by Sophocles are original, full-length adaptions. Style: An Approach to Appreciating Theatre is the perfect resource for students of Theatre Appreciation, Introduction to Theatre, Theatrical Design, and Stagecraft courses"--
Acknowledgements -- What is theatre? -- What is style? -- Style : realism -- Realistic play : Trifles by Susan Glaspell -- Style : theatricalism -- Theatricalistic play : The insect play by the Brothers Capek, adapted by E. Bert Wallace -- Style : expressionism -- Expressionistic play : The hairy ape by Eugene O'Neill, adapted by E. Bert Wallace -- Style : classicism -- Classical play : Antigone by Sophocles, adapted by E. Bert Wallace -- Style : musical theatre -- Playwrights -- Directors -- Designers -- Actors and other collaborators.
P.B
P.B
Includes bibliographical references and index.
Keywords: Theater; Drama; Drama; Theater